Recensione del libro "Straight up. Percorsi strategici per nuove imprese" - Tonino, Pencarelli (Piccola Impresa / Small Business, 2019)
In recent years, also following the economic crisis that began in 2008, which led to numerous bankruptcies of companies, especially the smaller ones, with a consequent significant reduction in the production base of our country, interest in the phenomenon of creation of new businesses. The italian legislator since 2006 has approved a series of regulations in support of the so-called innovative start-ups, in order to launch new business initiatives, to keep it going quickly, tenaciously. , direct, ie by adopting the "Straight Up" perspective. "Straight Up" is the title and the leitmotif of the interesting and stimulating monographic work of Elita Schillaci and Marco Romano, experts of the entrepreneurial phenomenon associated with the creation of new businesses and scholars of economics and business management at the University of Catania. The authors have organized the volume trying to answer four basic questions that in their opinion should be addressed by addressing the topic: Who, Why, How, What.